Reproducing Kernel Method for Fractional Riccati Differential Equations - X. Y. Li; B. Y. Wu; R. T. Wang (Abstract and Applied Analysis)
This paper is devoted to a new numerical method for fractional Riccati differential equations. The method combines the reproducing kernel method and the quasilinearization technique. Its main advantage is that it can produce good approximations in a larger interval, rather than a local vicinity of the initial position. Numerical results are compared with some existing methods to show the accuracy and effectiveness of the present method.